Interferences between breathing, experimental dyspnoea and bodily self-consciousness - Allard, Etienne (Sci Rep, 2017)
Dyspnoea, a subjective experience of breathing discomfort, is a most distressing symptom. It implicates complex cortical networks that partially overlap with those underlying bodily self-consciousness, the experience that the body is one’s own within a given location (self-identification and self-location, respectively). Breathing as an interoceptive signal contributes to bodily self-consciousness: we predicted that inducing experimental dyspnoea would modify or disrupt this contribution. We also predicted that manipulating bodily self-consciousness with respiratory-visual stimulation would possibly attenuate dyspnoea. Twenty-five healthy volunteers were exposed to synchronous and asynchronous respiratory-visual illumination of an avatar during normal breathing and mechanically loaded breathing that elicited dyspnoea. During normal breathing, synchronous respiratory-visual stimulation induced illusory self-identification with the avatar and an illusory location of the subjects’ breathing towards the avatar. This did not occur when respiratory-visual stimulation was performed during dyspnoea-inducing loaded breathing. In this condition, the affective impact of dyspnoea was attenuated by respiratory-visual stimulation, particularly when asynchronous. This study replicates and reinforces previous studies about the integration of interoceptive and exteroceptive signals in the construction of bodily self-consciousness. It confirms the existence of interferences between experimental dyspnoea and cognitive functions. It suggests that respiratory-visual stimulation should be tested as a non-pharmacological approach of dyspnoea treatment.